Antiretroviral-based HIV prevention strategies for women. Issue 10 (October 2010) - Chirenje, Z Mike; Marrazzo, Jeanne; Parikh, Urvi M
Almost three decades have elapsed since researchers identified HIV as the cause of AIDS, with current estimates from UNAIDS that 33.4 million adults were living with HIV/AIDS in 2008. Two-thirds of this burden of disease is in Sub-Saharan Africa, and 60% of those infected are women. The disease still remains incurable and current prevention strategies including abstinence, male/female condom use and male circumcision are only partially effective. New strategies to curb the epidemic are urgently needed. Scientists are diligently exploring HIV prevention methods that are safe, effective and affordable. These new biological interventions include oral pre-exposure prophylaxis using oral antiretroviral (ARV) drugs, ARV treatment in HIV-infected persons to reduce transmission and topical ARV-based microbicide formulations.